Female genital injury: which findings have to be considered physiological using colposcopy with and without toluidine blue dye? - Berlit, Clara; Sütterlin, Marc; Yen, Kathrin; Weiß, Christel; Heinze, Sarah; Tuschy, Benjamin; Berlit, Sebastian (Forensic science, medicine, and pathology, 2021)
This study aimed to assess the validity and efficacy of blue dye in colposcopic assessment of genital injury in pre- and postmenopausal women with and without history of consensual sexual intercourse. Two hundred women were prospectively enrolled and examined colposcopically with and without toluidine blue dye in order to detect and categorize genital lesions (laceration, bruise and abrasion). Examination of genital trauma was accomplished in a standardized way and findings were photo documented. A wide range of influencing factors with a potential impact on prevalence and nature of genital injury was recorded beforehand using a questionnaire. The frequency of diagnostic injury differed substantially depending on the examination technique, ranging from 9% using colposcopic magnification only to 28% with the additional use of toluidine blue dye. A vertical laceration affecting the posterior fourchette was the most frequent lesion detected (17%, n = 32). Menopausal status seems to have significant impact on genital injury prevalence (p = 0.0165), as 42% (16/ 38) of postmenopausal compared to 24% (36/ 151) of premenopausal women had at least one genital lesion. Furthermore, vaginal medication (p = 0.0369), vaginal dryness (p = 0.0228), dyspareunia (p = 0.0234) and low frequency of sexual intercourse (p = 0.0022) were found to significantly correlate with the presence of genital lesions. According to our findings, standardized colposcopy in combination with toluidine blue dye facilitates accurate assessment of genital lesions. Genital trauma situated at another site than the posterior part of the vaginal introitus seems to be uncommon after consensual intercourse.
Published: 06 October 2021
Gesehen am 13.12.2022